Numerical Representations and User Behaviour in Social Networking Sites: Towards a Multi- Theoretical Research Framework - Sjöklint, Mimmi; Constantiou, Ioanna; Trier, Matthias (ECIS 2013 Proceedings)
The new technological enhancements and the accessibility to varieties of online applications, enable users to collect personal data and perform self-evaluation through test, comparison and experimentation. The sparked interest in numbers and numbers as self-representative visualisations is prominent in social networking sites, which are the empirical setting for the present study. This paper sets out to establish a multi-theoretical framework which enables the investigation of emerging phenomena of the role of numbers in social networking sites. The proposed framework rests on three theoretical pillars: self-determination theory, heuristic decision making and behavioural economics. A discussion departs from these convictions to investigate user reactions and behaviour when faced with numerical representations in the SNS.
Keywords: User Behaviour; Social Networking Sites; Numerical Representations; Multi-Theoretical Framework; Quantified Self; Pointification

Does Financial Statement Audit Reduce the Cost of Debt of Private Firms? - Kosi, Urska; Koren, Jerney; Valentincic, Aljosa
This study examines the effect of audit on private firms’ cost of debt. We use a sample of 1,949 small private firms operating in the period 2006-2010 with optional financial statement audit. High quality data allows us to construct a more precise interest rate measure than existing studies employ. After controlling for obvious sources of demand for voluntary audits (ownership complexity, subsidiary status, bank relations), we find a robust central result that voluntary audits increase rather than decrease the cost of debt financing, contrary to several existing studies. This finding indicates that voluntary audits are generally treated as “adopting a label” and penalised by creditors, regardless of the perceived auditor quality as a result of the lemon problem in the audit market. Even Big-4 audits increase the cost of debt, likely as a result due to the lemon problem in the audit market, although the increase is smaller than for non-Big-4 audits. The results are sensitive to the estimation method used (OLS, Heckman’s two-step, PSM) and (sub-)sample selection. We show that disregarding the underlying assumptions of these estimation methods may lead to incorrect inferences. Additional analyses show that audited firms’ reported earnings are less informative about future operating performance than earnings of their unaudited counterparts. Our results also indicate that results are sensitive to cost of debt definition and this might have affected the results reported in the existing literature.
Keywords: private firms; voluntary audit; cost of debt; self-selection bias; lemon problem

Educating attention: recruiting, maintaining, and framing eye contact in early natural mother-infant interactions - Nomikou, Iris; Rohlfing, Katharina; Szufnarowska, Joanna (Interaction Studies)
In a longitudinal naturalistic study, we observed German mothers interacting with their infants when they were 3 and 6 months old. Pursuing the idea that infants’ attention is socialized in everyday interactions, we explored whether eye contact is reinforced selectively by behavioral modification in the input provided to infants. Applying a microanalytical approach focusing on the sequential organization of interaction, we explored how the mother draws the infant’s attention to herself and how she tries to maintain attention when the infant is looking at her. Results showed that eye contact is reinforced by specific infant-directed practices: interrogatives and conversational openings, multimodal stimulation, repetition, and imitation. In addition, these practices are contingent on the infant’s own behavior. By comparing the two data points (3 and 6 months), we showed how the education of attention evolves hand-in-hand with the developing capacities of the infant.
Keywords: interactional adaptation; multimodal input; social learning; ecology of attention; eye contact

DoA-Based Microphone Array Position Self-Calibration Using Circular Statistic - Jacob, Florian; Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (38th International Conference on Acoustics, Speech, and Signal Processing (ICASSP 2013))
In this paper we propose an approach to retrieve the absolute geometry of an acoustic sensor network, consisting of spatially distributed microphone arrays, from reverberant speech input. The calibration relies on direction of arrival measurements of the individual arrays. The proposed calibration algorithm is derived from a maximum-likelihood approach employing circular statistics. Since a sensor node consists of a microphone array with known intra-array geometry, we are able to obtain an absolute geometry estimate, including angles and distances. Simulation results demonstrate the effectiveness of the approach.
Keywords: Geometry calibration; microphone arrays; position self-calibration

Model-driven Performance Engineering of Self-adaptive Systems: A Survey - Becker, Matthias; Luckey, Markus; Becker, Steffen ({Proceedings of the 8th International ACM SIGSOFT Conference on Quality of Software Architectures (QoSA)})
Keywords: model-driven performance engineering; self-*; Self-adaptation; software performance

Technology Mediation in Service Delivery: A New Typology and an Agenda for Managers and Academics. - Schumann, Jan H; Wünderlich, Nancy; Wangenheim, Florian (Technovation)
The role of information and communication technology for economic growth has been emphasized repeatedly. Technological breakthroughs have generated new forms of services, such as self-services or remote services. Although these encounters are qualitatively different from traditional service provision, prior service management literature thus far had paid little attention to theory development and the systematization of technology-based service encounters. To fill this research gap, the present study outlines how new types of technology-based services fit into existing service typologies and provides an extension of existing frameworks to capture their unique characteristics. These insights in turn offer managerial implications and highlight open research questions.
Keywords: Services; Remote services; Self-services; Technology mediation

Non-perturbing cavitation detection / monitoring in sonochemical reactors - Bornmann, Peter; Hemsel, Tobias; Sextro, Walter; Maeda, Takafumi; Morita, Takeshi (Ultrasonics Symposium (IUS), 2012 IEEE International)
To optimize the ultrasound irradiation for cavitation based ultrasound applications like sonochemistry or ultrasound cleaning, the correlation between cavitation intensity and the resulting effect on the process is of interest. Furthermore, changing conditions like temperature and pressure result in varying acoustic properties of the liquid. That might necessitate an adaption of the ultrasound irradiation. To detect such changes during operation, process monitoring is desired. Labor intensive processes, that might be carried out for several hours, also require process monitoring to increase their reliability by detection of changes or malfunctions during operation. In some applications cavitation detection and monitoring can be achieved by the application of sensors in the sound field. Though the application of sensors is possible, this necessitates modifications on the system and the sensor might disturb the sound field. In other applications harsh, process conditions prohibit the application of sensors in the sound field. Therefore alternative techniques for cavitation detection and monitoring are desired. The applicability of an external microphone and a self-sensing ultrasound transducer for cavitation detection were experimentally investigated. Both methods were found to be suitable and easily applicable.
Keywords: cavitation; chemical reactors; microphones; process monitoring; reliability; ultrasonic applications; ultrasonic waves; acoustic properties; cavitation based ultrasound applications; cavitation intensity; change detection reliability; external microphone; malfunction detection reliability; nonperturbing cavitation detection; nonperturbing cavitation monitoring; process monitoring; self-sensing ultrasound transducer; sonochemical reactors; sonochemistry; ultrasound cleaning; ultrasound irradiation; Acoustics; Liquids; Monitoring; Sensors; Sonar equipment; Transducers; Ultrasonic imaging

Probabilistic Planning for Predictive Condition Monitoring and Adaptation Within the Self-Optimizing Energy Management of an Autonomous Railway Vehicle - Klöpper, Benjamin; Sondermann-Wölke, Christoph; Romaus, Christoph (Journal of Robotics and Mechatronics)
Self-optimizing mechatronic systems are a new class of technical systems. On the one hand, new challenges regarding dependability arise from their additional complexity and adaptivity. On the other hand, their abilities enable new concepts and methods to improve the dependability of mechatronic systems. This paper introduces a multi-level dependability concept for selfoptimizing mechatronic systems and shows how probabilistic planning can be used to improve the availability and reliability of systems in the operating phase. The general idea to improve the availability of autonomous systems by applying probabilistic planning methods to avoid energy shortages is exemplified on the example of an innovative railway vehicle.
Keywords: self-optimizing systems; dependability; probabilistic planning; energy management

Microphone Array Position Self-Calibration from Reverberant Speech Input - Jacob, Florian; Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (International Workshop on Acoustic Signal Enhancement (IWAENC 2012))
In this paper we propose an approach to retrieve the geometry of an acoustic sensor network consisting of spatially distributed microphone arrays from unconstrained speech input. The calibration relies on Direction of Arrival (DoA) measurements which do not require a clock synchronization among the sensor nodes. The calibration problem is formulated as a cost function optimization task, which minimizes the squared differences between measured and predicted observations and additionally avoids the existence of minima that correspond to mirrored versions of the actual sensor orientations. Further, outlier measurements caused by reverberation are mitigated by a Random Sample Consensus (RANSAC) approach. The experimental results show a mean positioning error of at most 25 cm even in highly reverberant environments.
Keywords: Unsupervised; geometry calibration; microphone arrays; position self-calibration

Intentionally positioned self-assembled InAs quantum dots in an electroluminescent p–i–n junction diode - Mehta, Minisha; Reuter, Dirk; Melnikov, Alexander; Wieck, Andreas D.; Michaelis de Vasconcellos, Steffen; Baumgarten, Tim; Zrenner, Artur; Meier, Cedrik (Physica E: Low-dimensional Systems and Nanostructures)
An intentional positioning of optically active quantum dots using site-selective growth by a combination of molecular beam epitaxy (MBE) and focused ion beam (FIB) implantation in an all-ultra-high-vacuum (UHV) setup has been successfully demonstrated. A square array of periodic holes on GaAs substrate was fabricated with FIB of 30 keV ions followed by an in situ annealing step. Subsequently, the patterned holes were overgrown with an optimized amount of InAs in order to achieve site-selective growth of the QDs on the patterned holes. Under well-optimized conditions, a selectivity of single quantum dot growth in the patterned holes of 52% was achieved. Thereafter, carrier injection and subsequent radiative recombination from the positioned InAs/GaAs self-assembled QDs was investigated by embedding the QDs in the intrinsic part of a GaAs-based p–i–n junction device. Electroluminescence spectra taken at 77 K show interband transitions up to the fifth excited state from the QDs.
Keywords: Molecular beam epitaxy; Focused ion beam; Self-assembled quantum dot; Electroluminescence